Litsa vlasti . Litsa vlasti . Faces of Power . Лица власти - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
This program was broadcast by Ostankino television (Moscow) in the Russian Federation and recorded by the moniotring group at the Research Institute of Radio Free Europe/Radio Liberty in Munich as part of their effort to track and analyze the official media of the countires of the former Soviet Union. Передача Российской государственной телевизионной и радиовещательной компании (РГТРК) "Останкино" (Москва, Российская Федерация) была записана группой мониторинга Исследовательского Института радиостанции Свободная Европа/Свобода (Мюнхен) как часть проекта по анализу официальных средств информации стран бывшего Советского Союза. Discussion of the problem of freedom of speech on television and radio. Featured in the program: Molostvov, Mikhail (People's Deputy); Ivanov, Sergei (People's Deputy); Eremin, Igor' (People's Deputy) Обсуждение проблемы свободы слова на телевидении и радио. В программе участвуют: Молоствов, Михаил (Народный депутат); Иванов, Сергей (Народный депутат); Еремин, Игорь (Народный депутат)